2017
DOI: 10.1039/c7ra09349g
|View full text |Cite
|
Sign up to set email alerts
|

Novel iodine-doped reduced graphene oxide anode for sodium ion batteries

Abstract: It is reported for the first time that iodine-doped reduced graphene oxide (I-rGO) has been designed as an anode material for sodium ion batteries (SIBs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Therefore, the resulting Fe 3 S 4 /RGO anode was shown to be capable of a reversible charge capacity of more than 1320 mA h g À1 over 275 cycles. 122 It is worth mentioning that besides LIBs there is growing interest in realizing other types of RGO based batteries such as sodium ion batteries (SIBs), 123,[125][126][127] lithium-sulfur batteries (LiSBs) 124 or aluminum batteries. 128 Li et al have suggested that SIBs are feasible when they have fabricated a Fe 2 O 3 /RGO composite anode (shown in Fig.…”
Section: Rgo -A Key Component In Electrode Structures Used In Various...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the resulting Fe 3 S 4 /RGO anode was shown to be capable of a reversible charge capacity of more than 1320 mA h g À1 over 275 cycles. 122 It is worth mentioning that besides LIBs there is growing interest in realizing other types of RGO based batteries such as sodium ion batteries (SIBs), 123,[125][126][127] lithium-sulfur batteries (LiSBs) 124 or aluminum batteries. 128 Li et al have suggested that SIBs are feasible when they have fabricated a Fe 2 O 3 /RGO composite anode (shown in Fig.…”
Section: Rgo -A Key Component In Electrode Structures Used In Various...mentioning
confidence: 99%
“…Therefore, the iodine/RGO anode reached a reversible capacity of 270 mA h g À1 at 50 mA g À1 and a cycling capacity of over 210 mA h g À1 after 100 cycles. 127 Moreover, new hybrids obtained through reduction of GO with the emphasis on encapsulation of CuP 2 nanoparticles into 3D graphene networks recently launched novel concepts in SIBs. 129 The fabricated electrodes could deliver a reversible capacity of over 800 mA h g À1 at 0.1 A g À1 .…”
Section: Rgo -A Key Component In Electrode Structures Used In Various...mentioning
confidence: 99%
“…After I 2 treatment, PANI-I 2 (Figure 2d) presents two couples of peaks at about 618.2/629.9 eV and 620.2/631.3 eV in I 3d region, which are ascribed to I 3 − and I 5 − , respectively. 36,37 No Cl signals have been detected, suggesting the completely dedoping Cl − . (Figure S7) In addition, PANI exhibits a small specific surface area of 21 m 2 /g (Figure S8).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Iodine as a p‐type dopant can improve the conductivity of the graphene film through a charge transfer process. Meanwhile, the doping of iodine atoms created the defect evolution and the increase of the layer spacing, which increases surface area of the materials 9‐11 . Iodine/nitrogen co‐doped two‐dimensional wrinkled graphene was successfully synthesized via adsorbing iodine on the surface of graphite oxide, followed by pyrolysis at 950°C in ammonia gas atmosphere 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the doping of iodine atoms created the defect evolution and the increase of the layer spacing, which increases surface area of the materials. [9][10][11] Iodine/nitrogen co-doped twodimensional wrinkled graphene was successfully synthesized via adsorbing iodine on the surface of graphite oxide, followed by pyrolysis at 950 C in ammonia gas atmosphere. 12 Through a simple hydrothermal process, iodine-doped polyaniline-reduced graphene oxide composite hydrogel was fabricated after adding elemental iodine into graphene oxide suspension at 120 C and the specific capacitance of the resulted sample was as high as 712.5 FÁg À1 at 1 AÁg À1 .…”
Section: Introductionmentioning
confidence: 99%